2001
DOI: 10.1007/s003830000395
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease presenting as entero-enteral intussusception

Abstract: Cramping abdominal pain with intermittent intestinal obstruction finally prompted investigation in a 4 1/2-year-old boy with severe failure to thrive (FTT). An entero-enteric intussusception was corrected, and celiac disease was identified as the cause of his inanition. Concomitant FTT and cramping abdominal pain should prompt investigation for celiac disease and small-bowel intussusception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
1
7
0
3
Order By: Relevance
“…Underlying gastrointestinal abnormalities or focal lead points causing small-bowel intussusception are rarely detected sonographically, but these findings include Meckel's diverticulum, duplication cyst, small-bowel polyp, lymphoma, and jejunal feeding tubes. More diffuse pathologic findings are lymphoid hyperplasia secondary to celiac disease, cystic fibrosis, Henoch-Schönlein purpura, and gastroenteritis [8][9][10][11][12][13]. Although rarely detected sonographically, lead points were found at surgery in eight (42%) of 19 surgical cases in the series described by Ko et al [7] and in nine (69%) of our 13 cases.…”
Section: Discussionmentioning
confidence: 70%
“…Underlying gastrointestinal abnormalities or focal lead points causing small-bowel intussusception are rarely detected sonographically, but these findings include Meckel's diverticulum, duplication cyst, small-bowel polyp, lymphoma, and jejunal feeding tubes. More diffuse pathologic findings are lymphoid hyperplasia secondary to celiac disease, cystic fibrosis, Henoch-Schönlein purpura, and gastroenteritis [8][9][10][11][12][13]. Although rarely detected sonographically, lead points were found at surgery in eight (42%) of 19 surgical cases in the series described by Ko et al [7] and in nine (69%) of our 13 cases.…”
Section: Discussionmentioning
confidence: 70%
“…The small-bowel intussusception can be transient and self limiting if it is less than 3 cm long [6]. A common feature of intussusception in CD is its recurrent character [14][15][16]. The association between acute bowel intussusception and CD has been often described in children [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Then Mushtaq et al [4] reported 3 children with spontaneously resolving small bowel intussusception in association with celiac disease and suggested that the finding of transient small bowel intussusception should have need of prompt investigation for celiac disease. Another 6 cases of intussusception whose initial presentation of celiac disease was reported in pediatric age group in English literature [5-10]. Here, I report two consecutive children with initial presentation of gastrointestinal obstruction due to intussusception, who proved later to have celiac disease.…”
Section: Introductionmentioning
confidence: 90%